Improvement in mood symptoms ​after post‐bariatric surgery among people with obesity: A systematic review and meta‐analysis. Issue 8 (4th May 2021) - Loh, Huai Heng; Francis, Benedict; Lim, Lee‐Ling; Lim, Quan Hziung; Yee, Anne; Loh, Huai Seng
Abstract: Aims: We aimed to examine if bariatric surgery was associated with a reduction in the prevalence of depressive and anxiety symptoms among people with obesity. Materials and Methods: We pooled data from 49 studies involving 11, 255 people with obesity who underwent bariatric surgery. The study outcomes were the prevalence of depressive and anxiety symptoms among these patients pre‐ and post‐surgery. Results: There was a significant reduction in body mass index (BMI) post‐operatively (pooled d +: −13.3 kg/m 2 [95% confidence interval [CI] 15.19, −11.47], p  < 0.001). The pooled proportion of patients with anxiety symptoms reduced from 24.5% pre‐operatively to 16.9% post‐operatively, with an odds ratio (OR) of 0.58 (95% CI 0.51, 0.67, p  < 0.001). The reduction remained significant in women aged ≥40 years and irrespective of post‐operative BMI. There were significant reductions in Hospital Anxiety and Depression Score (HADS) (anxiety component) by 0.64 (pooled d +: −0.64 [95% CI −1.06, −0.22], p  = 0.003) and Generalized Anxiety Disorder Assessment‐7 score by 0.54 (pooled d +: −0.54 [95% CI −0.64, −0.44], p  < 0.001). The pooled proportion of depressive symptoms reduced from 34.7% pre‐operatively to 20.4% post‐operatively, with an OR of 0.49 (95% CI 0.37, 0.65, p  < 0.001). The reduction remained significant irrespective of patient's age and post‐operative BMI. There were also significant reductions in HADS score (depressive component) (pooled d +: −1.34 [95% CI −1.93, −0.76], p  < 0.001), Beck's Depression Inventory score (pooled d +: −1.04 [95% CI −1.46, −0.63], p  < 0.001) and Patient Health Questionnaire‐9 score (pooled d +: −1.11 [95% CI −1.21, −1.01], p  < 0.001). Conclusion: Bariatric surgery was associated with significant reduction in the prevalence and severity of depressive and anxiety symptoms among people with obesity.